Structural and Technological Change in Money Demand - Lieberman, Charles (American Economic Review, 1979)
Although demand for money equations have traditionally been regarded as exceptionally stable, the literature abounds with empirical evidence of structural shifts and apparent trends in some of the coefficients over time. Subperiod estimates of long-term studies often yield different coefficients or suggest secular trends in the coefficients. Other studies report structural shifts or variables which are significant only during particular periods. And while numerous other instabilities have vanished along with revisions in the data, the 1974 instability is too large to be so obliging. Thus, the latest apparent instability is hardly without precedent. One possible source of these instabilities is the omission from the estimated equations of a measure of technological change which reduces over time the real cost of transactions in the management of money balances. The real cost of transactions plays a substantial role in explaining money holdings in the standard inventory theoretic models of money demand. The omission of a key explanatory variable from the estimation produces a misspecified equation which may result in biased coefficient estimates. While the sources of the most recent instability in money demand equations may be due to a structural shift, as suggested in several studies, it may also be due in part to an omitted technological change measure. This paper tests the usefulness of some technological change proxies and examines the forecasting ability of these modified models over the difficult post-1974 period. A Shiller lag specification is employed to obtain a better specification of the dynamic properties of money demand. Although the technological change proxies do improve the equations, the findings support the existence of another structural shift in money demand. The results nevertheless provide some hope that a fairly standard money demand equation, with only minor adjustments, may once again be capable of providing satisfactory forecasts, at least for the present.